ENHANCING LEARNING EFFECTIVENESS THROUGH ADAPTIVE LEARNING PLATFORMS AND EMERGING COMPUTER TECHNOLOGIES IN EDUCATION - Isaeva, Rapiia; Karasartova, Nazgul; Dznunusnalieva, Kalyibubu; Mirzoeva, Kabira; Mokliuk, Mykola (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The integration of adaptive learning platforms and emerging computer technologies has transformed education by personalizing learning experiences and increasing accessibility. However, challenges such as uneven access, inadequate teacher training, and technical limitations hinder their full potential. This study examines the impact of major educational platforms (Coursera, Khan Academy, edX) and adaptive technologies on the learning process, aiming to assess their effectiveness in diverse educational contexts. A mixed-methods approach was employed, combining qualitative content analysis of educational platforms such as Coursera, Khan Academy, and edX with quantitative assessment of their features, engagement levels, and effectiveness. The study analyzed data from educational institutions in Kyrgyzstan, Ukraine, and Azerbaijan, focusing on the role of analytics, interactive elements, and gamification in enhancing learning outcomes. Findings indicate that adaptive platforms enhance accessibility and flexibility in learning while offering real-time analytics for personalized feedback. Virtual labs, such as those utilizing the Quanser QNET DC Motor Control Board, demonstrated the feasibility of remote practical training. However, successful implementation depends on comprehensive planning, infrastructure readiness, and continuous professional development for educators. The study contributes to understanding the role of adaptive learning in addressing educational disparities. It highlights the necessity of institutional support and teacher training for the effective use of these technologies. Novel insights include the potential of integrating AI-driven analytics to optimize personalized learning experiences. Future research should explore long-term impacts on student engagement and academic performance, particularly in under-resourced educational settings.